Circumcoronenes. Issue 19 (24th March 2023) - Zou, Ya; Hou, Xudong; Wei, Haipeng; Shao, Jiawei; Jiang, Qing; Ren, Longbin; Wu, Jishan
Abstract: Circumcoronene, a hexagonal graphene fragment with six zigzag edges, has been the focus of theoretical studies for many years, but its synthesis in solution has remained a challenge. In this study, we present a facile method for synthesizing three derivatives of circumcoronene using Brønsted/Lewis acid‐mediated cyclization of vinyl ether or alkyne. Their structures were confirmed through X‐ray crystallographic analysis. Bond length analysis, NMR measurement, and theoretical calculations showed that circumcoronene mostly follows Clar's bonding model and exhibits dominant local aromaticity. Its absorption and emission spectra are similar to those of the smaller hexagonal coronene due to its six‐fold symmetry. Abstract : Circumcoronenes were finally obtained by solution‐phase synthesis and isolated in crystalline form. The Brønsted/Lewis acid‐mediated cyclization of vinyl ethers or alkynes was employed as the key reaction. X‐ray analysis, NMR and theoretical calculations confirmed a structure with seven aromatic sextets and six localized K‐region double bonds.